Sub-Regional Economic Cooperation in Southeast Asia: ITRO's Effect to Rubher's FDI lnflows & Indonesia's Rubber Economic Multipliers - Verico, Kiki; Batubara, Williater Leonardo (Economics and Finance in Indonesia, 2010)
.